The Effect Of The Implementation Of Artificial Intelligence In Stock Trading Strategies On Profitability: A Managerial Perspective In The Indonesian Capital Market - Primas Arisandy Nugraha; Abdul Moin; Risma Rosehan (LP2M IAIN Palopo, 2025)
The following study aims to analyze the impact of artificial intelligence (AI) implementation, limited infrastructure and human resource (HR) skills, capital market regulations, and managerial decisions on profitability in stock trading strategies in the Indonesian capital market. The study employed a quantitative approach by distributing questionnaires to 100 respondents, including individual investors, investment managers, financial analysts, and financial institution professionals. Data were analyzed using multiple linear regression using SPSS version 25 software. The study's findings indicate that artificial intelligence (AI) implementation, capital market regulations, and managerial decisions have a positive and significant impact on profitability in stock trading strategies. Conversely, limited infrastructure and human resource (HR) skills have no significant impact. Simultaneously, the four independent variables explain 81% of the variation in profitability, with the remaining portion influenced by several other variables outside the study. The following study makes a theoretical contribution by enriching the literature on the role of AI and managerial factors in increasing investment profitability. Practically, these findings emphasize the importance of integrated AI adoption, coupled with strong capital market regulations and sound managerial decisions, to support the success of stock trading strategies in the digital era.